Fetal anencephaly with umbilical cord attached to cerebrovasculosa area: autopsy report - Stephan Philip L. Altmayer; McArthur Alex Barrow; Maiara A. Floriani; Glauco K. Nagata; Matheus Zanon; André C. Cunha; Paulo Renato Krahl Fell; Cristine Dietrich; Paulo Ricardo G. Zen; Rafael Fabiano M. Rosa (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT Our aim was to report the unusual case of an anencephalic fetus that was born with the umbilical cord attached to its cephalic pole. The patient was a 16-year-old pregnant woman. Ultrasound evaluation at 17 weeks revealed a single fetus without cranial vault and brain parenchyma, compatible with anencephaly. Postnatal evaluation, through an autopsy, was consistent with this diagnosis. Moreover, it was observed that the umbilical cord was attached to the area cerebrovasculosa and there was the presence of a fibrous tissue, suggestive of an amniotic band. We have found only one similar case described in the literature.